A Comparison of Intergenerational Mobility Curves in Germany, Norway, Sweden, and the US1. (18th July 2016) - Bratberg, Espen; Davis, Jonathan; Mazumder, Bhashkar; Nybom, Martin; Schnitzlein, Daniel D.; Vaage, Kjell
Abstract: We examine intergenerational mobility differences between Germany, Norway, Sweden, and the US. Using ranks, we find that the US is substantially less intergenerationally mobile than the three European countries and that the most mobile region of the US is less mobile than the least mobile regions of Norway and Sweden. Using a linear estimator of income share mobility, we find that the four countries have very similar rates of intergenerational mobility. However, when we use non‐parametric versions of rank and income share mobility, we find that the US tends to experience lower upward mobility at the bottom of the income distribution than Norway and Sweden.